Biofeedback in partial weight bearing: Validity of 3 different devices - van Lieshout, R.; Stukstette, M. J.; de Bie, R. A.; Vanwanseele, B.; Pisters, M. F. (Journal of Orthopaedic & Sports Physical Therapy, 2016)
Study Design: Controlled laboratory study to assess criterion-related validity, with a cross-sectional within-subject design. Background: Patients with orthopaedic conditions have difficulties complying with partial weight-bearing instructions. Technological advances have resulted in biofeedback devices that offer real-time feedback. However, the accuracy of these devices is mostly unknown. Inaccurate feedback can result in incorrect lower-limb loading and may lead to delayed healing. Objectives: To investigate validity of peak force measurements obtained using 3 different biofeedback devices under varying levels of partial weight-bearing categories. Methods: Validity of 3 biofeedback devices (OpenGo science, SmartStep, and SensiStep) was assessed. Healthy participants were instructed to walk at a self-selected speed with crutches under 3 different weight-bearing conditions, categorized as a percentage range of body weight: 1% to 20%, greater than 20% to 50%, and greater than 50% to 75%. Peak force data from the biofeedback devices were compared with the peak vertical ground reaction force measured with a force plate. Criterion validity was estimated using simple and regression-based Bland-Altman 95% limits of agreement and weighted kappas. Results: Fifty-five healthy adults (58% male) participated. Agreement with the gold standard was substantial for the SmartStep, moderate for OpenGo science, and slight for SensiStep (weighted ± = 0.76, 0.58, and 0.19, respectively). For the 1% to 20% and greater than 20% to 50% weight-bearing categories, both the OpenGo science and SmartStep had acceptable limits of agreement. For the weight-bearing category greater than 50% to 75%, none of the devices had acceptable agreement. Conclusion: The OpenGo science and SmartStep provided valid feedback in the lower weight-bearing categories, and the SensiStep showed poor validity of feedback in all weight-bearing categories.